EFFECT OF COMPUTER SIMULATIONS PACKAGE ON SECONDARY SCHOOL STUDENTS’ ACADEMIC ACHIEVEMENT IN PHYSICS IN ANAMBRA STATE (UNIZIK Journal of STM Education, 2025)
This study investigated the effect of Computer Simulation Package (CSP) on academic achievement of students in physics. The research design was quasi experimental research design, specifically, non-equivalent control group. The sample consisted of 65 senior secondary school two (SSII) students which is made up of 50 experimental group (28 males and 22 females) while control group was 15 students (2 males and 13 females) drawn from two co-educational secondary schools in Awka Education Zone of Anambra State. Instrument used for data collection was Physics Achievement Test (PAT) which was validated by physics education lecturers from science education department and pilot-tested in another zone. Scores obtained from pre-test and post-test were used to estimate the instrument reliability and its reliability co-efficient was found to be 0.88 using Kuder Richardson formula 20. The hypotheses were tested at 0.05 level of significance using ANCOVA. The result revealed that computer simulation was more effective in enhancing students’ academic achievement in physics than lecture method; there was no significant difference on students’ academic achievement due to gender. It was recommended that computer simulation package should be adopted for teaching physics concepts. Based on the findings, it was concluded that computer simulation should be employed in physics teaching in order to improve the students’ academic achievement and increase their retention capacity and also the government and education stakeholders should encourage the use of computer simulation package in teaching physics in secondary schools.
Keywords: Academic Achievement, Computer Simulation Package, Lecture Method, Physics